Grupo topológico - Dutra, Aline Cristina Bertoncelo [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Neste trabalho tratamos do objeto matemático Grupo Topológico. Para este desenvolvimento, abordamos elementos básicos de Grupo e Espaço Topológico

In this work we consider the mathematical object Topological Group. For this development, we discuss the basic elements of the Group and Topological Space
Keywords: Topologia algebrica; Topologia; Álgebra; Algebraic topology; Topology